IMPROVING HUMAN RESOURCE PERFORMANCE THROUGH JOB BURNOUT MODERATED BY COPING STRATEGY AND COMMITMENT AT UPP CLASS III OFFICE OF JEPARA, PATI, AND REMBANG - Sutarto Sutarto; Nunung Ghoniyah (IJIBE (International Journal of Islamic Business Ethics), 2017)
The operational performance of service department, parts of goods, and passengers at UPP Class III Office of Jepara, Pati and Rembang decreased. The purpose of this research is to test and analyze the improvement of HR performance through job burnout which is moderated coping strategy and commitment at the organizer office unit of Class III Port of Jepara Regency, Pati, and Rembang. The population of this study is all human resources in the third class Port of 106 human resources, including Jepara 49 people, Juana 33 people, and Rembang 34 people. Samples were taken from all of the population by sampling technique using census. The result of the research shows that Job Burnout has a positive influence on HR performance, positively significant commitment influencing HR performance, and there is no significant influence between Job Burnout on Human Resource performance which is moderated by Coping Strategy.Keywords : Job Burnout, Coping Strategy, Commitment, Performance